2010
DOI: 10.1371/journal.pone.0012160
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Actions of Others: The Electrodynamics of the Left and Right Hemispheres. A High-Density EEG Neuroimaging Study

Abstract: BackgroundWhen we observe an individual performing a motor act (e.g. grasping a cup) we get two types of information on the basis of how the motor act is done and the context: what the agent is doing (i.e. grasping) and the intention underlying it (i.e. grasping for drinking). Here we examined the temporal dynamics of the brain activations that follow the observation of a motor act and underlie the observer's capacity to understand what the agent is doing and why.Methodology/Principal FindingsVolunteers were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
77
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 70 publications
13
77
0
Order By: Relevance
“…Compelling neurophysiological and brain-imaging experiments also provide indirect evidence for the presence of similar motor understanding mechanisms in humans (Berchio et al, 2014;Cattaneo et al, 2007;Cattaneo, Sandrini, & Schwarzbach, 2010;Gazzola et al, 2007;Iacoboni et al, 2005;McGarry, Russo, Schalles, & Pineda, 2012;Ortigue, Sinigaglia, Rizzolatti, & Grafton, 2010;Peeters et al, 2009;Senna, Bolognini, & Maravita, 2014;Théoret et al, 2005; for a review, see Rizzolatti et al, 2014). Taken together, these data suggest that also in humans the cortical motor system does not exclusively encode the kinematics of actions but also-and more intriguingly-its meaning.…”
mentioning
confidence: 80%
“…Compelling neurophysiological and brain-imaging experiments also provide indirect evidence for the presence of similar motor understanding mechanisms in humans (Berchio et al, 2014;Cattaneo et al, 2007;Cattaneo, Sandrini, & Schwarzbach, 2010;Gazzola et al, 2007;Iacoboni et al, 2005;McGarry, Russo, Schalles, & Pineda, 2012;Ortigue, Sinigaglia, Rizzolatti, & Grafton, 2010;Peeters et al, 2009;Senna, Bolognini, & Maravita, 2014;Théoret et al, 2005; for a review, see Rizzolatti et al, 2014). Taken together, these data suggest that also in humans the cortical motor system does not exclusively encode the kinematics of actions but also-and more intriguingly-its meaning.…”
mentioning
confidence: 80%
“…Recent theories of embodied cognition (i.e., implicit understanding of others' actions through our own past motor experiences) suggest one understands intention of others by shaping one's understanding and anticipation of actions performed by others based on one's own motor system (Jeannerod, 2001;Niedenthal, 2007;Grafton, 2009), which is a process that takes place in embodied cognition (Grafton, 2009;Rizzolatti & Sinigaglia, 2008;Jeannerod, 2000;Ortigue et al, 2010, Grafton, 2009. As Jackson and Decety (2004) initially noted, the existence of a system matching executed and perceived actions offers a parsimonious explanation of how one recognizes other people's intended actionsi.e., by a direct mapping of the visual representation of the observed action onto one's own motor representation of the same action.…”
mentioning
confidence: 99%
“…Inferring intentions of other people from the observation of their actions recruits an inferior fronto-parietal action observation network (AON) as well as a putative social network (SN) that includes the posterior superior temporal sulcus (STS), the temporoparietal junction (TPJ), the anterior paracingulate and also the cingulate cortex, a key prefrontal region subserving theory of mind (ToM). Furthermore, electrophysiological studies using high-density EEG recordings in healthy volunteers provide further information regarding the temporal dynamics between these two brain networks (AON and SN) for private intentions (Ortigue et al, 2009(Ortigue et al, , 2010Sabbagh et al, 2004a;Wang et al, , 2010. For instance, Ortigue et al recently showed the dynamic involvement of both the posterior superior temporal sulcus (pSTS) and inferior parietal lobe (IPL) at early stages of information processing for private intentions, and without a strict segregation between the AON and SN networks (Ortigue et al, 2009;.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that object words refer to the goal of actions, such enhancement in the object word condition provides further evidence that the MNS is associated with the encoding of the goal of action and high‐level cognitive process, such as inferring the intentions of others. The object of action is considered to be critical for understanding what the individual is doing (Ortigue, Sinigaglia, Rizzolatti, & Grafton, 2010; Ortigue, Thompson, Parasuraman, & Grafton, 2009). Our findings about the unique nature of the object word are therefore compatible with previous works that emphasized the goal understanding function of the MNS(Rizzolatti et al., 2014; Sperduti, Guionnet, Fossati, & Nadel, 2014).…”
Section: Discussionmentioning
confidence: 99%